2018
DOI: 10.1016/j.jtcvs.2017.11.103
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Fontan paradox: Addressing socioeconomic and racial disparities in patients with a single ventricle

Abstract: for the members of the Southwest Congenital Cardiac Consortium Feature Editor's Note-The Fontan operation, in many respects, is the signature operation for congenital heart surgeons. At our Heart Center, palliative operations leading up to the Fontan procedure, the Fontan procedure itself, and post-Fontan surgical interventions account for 20% of our congenital cardiac surgery case volume. Over the past 45 years, the Fontan operation has evolved steadily with numerous technical modifications as surgeons have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Relationships between obesity, race, and ethnicity and poor long-term outcomes in the Fontan population have been reported (41,42). Prior studies have not investigated hepatic steatosis in the context of FALD, though one reported it on histology (5).…”
Section: Survival and Risk Factor Analysismentioning
confidence: 99%
“…Relationships between obesity, race, and ethnicity and poor long-term outcomes in the Fontan population have been reported (41,42). Prior studies have not investigated hepatic steatosis in the context of FALD, though one reported it on histology (5).…”
Section: Survival and Risk Factor Analysismentioning
confidence: 99%
“…Although contemporary reports of Fontan palliation have demonstrated re-assuring long-term survival in selected groups of patients, 10 it is clear that specific subgroups fare worse with this approach. Atz et al 11 detailed the sobering long-term results among Fontan patients in Fontan 3 À the most recent installment of the PHN cross-sectional study. Despite overall good survival (90% at 9.4 years), there was a steady attrition in transplant-free survival.…”
Section: Surgical Pearlsmentioning
confidence: 99%
“…Comparably worse outcomes among African Americans and those in lower income quartiles are consistently reported following both congenital and acquired cardiac surgery. 29,30 Benavidez and colleagues 31 investigated race/ethnic disparities in outcomes following congenital heart surgery using the Kids Inpatient Database 2000. In this study, in-patient mortality was significantly increased in the black population compared with white ethnicity and regional geographic differences in racial/ethnic outcomes were apparent.…”
Section: Socioeconomic Disparities: Will Regionalization Widen the Access Gap?mentioning
confidence: 99%
“…In this study, in-patient mortality was significantly increased in the black population compared with white ethnicity and regional geographic differences in racial/ethnic outcomes were apparent. In the Benavidez study, socioeconomic status was not associated with increased risk of death, but as Karamlou and colleagues 29 discussed, studies of sociodemographic influence are often superficial (usually as a result of nongranular variable capture in most available datasets) and incompletely assess interactions among highly collinear or modifying factors. Building on this contention, we recently used the Pediatric Health Information Systems database to explore whether inflection points could be determined whereby race/ethnicity could be mitigated by positive modifiers, including discrete income level or more evolved programmatic/process factors on the one hand, or exacerbated by negative modifiers, including genetic abnormalities or center experience.…”
Section: Socioeconomic Disparities: Will Regionalization Widen the Access Gap?mentioning
confidence: 99%